Assessment of IL-8 and Some Biochemical Parameters in Breast Cancer Patients Post Chemotherapy - Salman, Evan Jawad; Yenzeel, Jabbar H. (Iraqi Journal of Science, 2026)
Background: One kind of cancer that starts as a proliferation of cells in the breast tissue, frequently developing into tumors, is breast cancer. With notable incidence rates in both industrialized and developing nations, it is the most prevalent cancer diagnosed in women globally. Environmental factors, lifestyle decisions, and hormones all increase the risk of breast cancer. It was demonstrated that individuals with breast cancer had greater levels of a number of pro-inflammatory cytokines, which explains their function in the pathogenicity of the disease and its therapy. The hypothesis of this study includes how chemotherapy for breast cancer affects the level of interleukins.Objective: This work aimed to investigate the change in the concentration of interleukin-8 and some biochemical parameters in breast cancer Iraqi patients after receiving different doses of chemotherapy.Materials and Methods: Seventy women diagnosed with breast cancer (35 newly diagnosed do not receive chemotherapy and 35 receiving different doses of chemotherapy) and thirty healthy were enrolled in this study during their attendance at the Oncology Hospital in the Medical City in Baghdad during the period from February 2024 to May 2024. All participants' ages ranged between (30 to70) years. Blood samples were collected from all women to measure the CBC and to evaluate the level of Interleukin- 8, vascular endothelial growth factor (VEGF), total antioxidant capacity (TAC), and C- reactive protein (CRP) level by using (ELISA) technique.Result: The results of the study expressed as the mean ± SE showed that WBC, RBC, Hb, neutrophil, lymphocytes, monocyte, and platelets highly significant (P≤0.01) decrease in breast cancer (newly diagnosis and chemotherapy-treated) women in comparison with control. Also, the results showed a highly significant (P≤0.01) increase in the level of IL-8, VEGF, and CRP in newly diagnosed and chemotherapy-treated breast cancer patients in comparison with the control. While the TAC showed a highly significant (P≤0.01) decrease in breast cancer patients in comparison with the control. Concerning the number of doses in chemotherapy-treated women, the result showed a significant (P≤0.01) decrease in CBC except for PLT(NS) in dose (9-20) as compared with dose (5-8) and dose (2-4). Also, the results showed a highly significant (P≤0.01) decrease in the level of IL-8 and TAC in dose (9-20) as compared with dose (5-8) and dose (2-4). While there was a significant (P≤0.01) increase in the level of CRP in dose (9-20) as compared to other doses. The level of VEGF showed a non-significant difference between different doses.Conclusion: It can be concluded that the changes in IL-8 and other biochemical parameters may be a good indicator for assessing the activity of breast cancer for newly diagnosed and chemotherapy-treated women.